Authorea
DOI: 10.22541/au.158497988.81945620
|View full text |Cite
|
Sign up to set email alerts
|

Seed mucilage evolution: diverse molecular mechanisms generate versatile ecological functions for particular environments

Abstract: Polysaccharidic mucilage is a widespread plant trait with diverse features, often present around plant structures in contact with the environment, providing numerous functions including protection and adhesion. Seed mucilage is released upon imbibition and therefore can play roles in the early seedling stages, but the evolutionary origins of this trait are unclear. Its presence in several flowering plant species suggests that it was present in their last common ancestor whereas the extreme inter-species morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The Ae. arabicum RNA‐seq demonstrated that in contrast to AearNARS1/2 and AearAP2 , TFs of the MYB‐bHLH‐WD40 (MWB) complex (Golz et al , 2018; Viudes et al , 2020; Voiniciuc et al , 2015) did not show a morph‐specific expression difference in flower samples (Figure 6a). Analysis of AearAP2 and AearNARS2 gene expression by RT‐qPCR at 1, 3 and 10 DAP (Figure 6b) not only confirmed that the transcript abundances differ at the flower stage (1 DAP), but also during all the subsequent early stages of seed coat differentiation, particularly at 3 DAP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ae. arabicum RNA‐seq demonstrated that in contrast to AearNARS1/2 and AearAP2 , TFs of the MYB‐bHLH‐WD40 (MWB) complex (Golz et al , 2018; Viudes et al , 2020; Voiniciuc et al , 2015) did not show a morph‐specific expression difference in flower samples (Figure 6a). Analysis of AearAP2 and AearNARS2 gene expression by RT‐qPCR at 1, 3 and 10 DAP (Figure 6b) not only confirmed that the transcript abundances differ at the flower stage (1 DAP), but also during all the subsequent early stages of seed coat differentiation, particularly at 3 DAP.…”
Section: Resultsmentioning
confidence: 99%
“…The default monomorphic ‘bauplan’ within the Brassicaceae is the development of dehiscent fruits (DEH) containing mucilaginous seeds (M + ) with A. thaliana and Lepidium sativum as examples (Ferrandiz et al , 1999; Mühlhausen et al , 2013; Scheler et al , 2015). The DEH/M + fruit/seed programme leads to fruit valve opening to release mature M + seeds as diaspores, which upon imbibition release mucilage from their outer seed coats (myxospermy) (Viudes et al , 2020; Western, 2012; Yang et al , 2012). Mutations in A. thaliana fruit development genes, such as the bHLH (basic helix–loop–helix) transcription factor (TF) INDEHISCENT and the MADS‐box TFs SHATTERPROOF1/2 ( SHP1/2 ), block fruit valve opening which phenotypically result in indehiscent fruits (IND) (Mühlhausen et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, three groups of scientists present systematic reviews of their understanding of the evolution of plant salinity tolerance at ecological, physiological, cellular and molecular levels (Caperta et al, 2020;Kotula, Garcia Caparros, Zorb, Colmer, & Flowers, 2020;Liu et al, 2020). Secretory structures (e.g., mucilage secretion, salt glands) are found in all angiosperm clades, with the potential to influence plant microenvironments, nutrient balance and stress tolerance (Galloway, Knox, & Krause, 2020;Viudes et al, 2020). Caperta and co-authors studied the link between secretory structures and salt tolerance in plants using the Plumbaginaceae family, which is adapted to a wide range of arid and saline habitats with at least 45 salt-tolerant species.…”
Section: Komatsu and Colleagues Reviewed The Functional Genomics Studiesmentioning
confidence: 99%
“…The review by Viudes and colleagues aimed at the under-studied field of myxodiaspory evolution, indicating the release of a polysaccharidic mucilage upon water imbibition of seeds (myxospermy) or fruits (myxocarpy) of myxodiasporous species may have potential roles in plant response to environmental stresses (Viudes, Burlat, & Dunand, 2020). A deep characterization of the molecular actors revealed the mucilage secretory cell (MSC) toolbox that underpins seed mucilage establishment in Arabidopsis thaliana (Francoz, Ranocha, Burlat, & Dunand, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation